Evaluation in Genetic Variation of Krachai by Sequence Related Amplified Polymorphism (SRAP) and Random Amplified Polymorphic DNA (RAPD) Techniques - Poothong, Sukalya; Mangphae, Waranya; Chanhom, Wuttikon; Nakkuntod, Maliwan (International Journal of Membrane Science and Technology, 2023)
Krachais are local name of Thai herb which are identified within 2 genera, namely Bosenbergia (white or red krachai) and Kaempferia (black krachai). The rhizome of Bosenbergia rotunda (L.) Mansf. contains major aromatic compounds against COVID19 but its many morphological characteristics such as leaves, stems and rhizome are like other species in same genus or family. In this study, a total of 13 accessions containing 5 samples of B. rotunda, 2 samples of Boesenbergia spp. and 3 samples of Kaempferia parviflora including 3 samples of other species in same family as outgroups were analyzed and clustered using sequence-related amplified polymorphism (SRAP) and random amplified polymorphism DNA (RAPD) markers. The results showed that 8 SRAP primers (M1E1, M1E2, M1E7, M2E10, M3E9, M5E1, M5E2 and M6E10) could generate 79 polymorphism bands with an average of 92.15% whereas a total of 5 RAPD primers (OPY04, OPY02, OPY04, JAT11 and JAT12) could give 64 polymorphisms with 100% as a percentage of the polymorphism band. The PIC of the SRAP marker (0.470) has a higher value than the RAPD marker (0.264). The highest similarity coefficients within genus Boesenbergia of 1.000 and 0.952 were obtained from SRAP and RAPD markers, respectively. The UPGMA dendrogram of SRAP and RAPD information among krachai presented 2 and 4 groups, respectively. The cluster of Boesenbergia was separated from K. parviflora and other species in same family. Furthermore, the results also pointed that Boesenbergia sp. from Phayao is in correct genus and is B. pandurata (Roxb.) Schltr. because of having red leaf while Boesenbergia sp. from Chiang Rai showed confusion between SRAP and RAPD data. It was concluded that SRAP and RAPD have great potential for the study of genetic diversity of Boesenbergia and other species in family Zingiberaceae.